2016
DOI: 10.1039/c6cy00457a
|View full text |Cite
|
Sign up to set email alerts
|

Non-directed aromatic C–H amination: catalytic and mechanistic studies enabled by Pd catalyst and reagent design

Abstract: This manuscript describes the systematic development of pyridine-type ligands, which promote the Pd catalyzed, non-directed amination of benzene in combination with novel, hydroxylamine-based electrophilic amination reagents. DFT calculations and mechanistic experiments provide insights into the factors influencing the arene C–H amination protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…N -Acetoxymethanesulfonamide was synthesized in analogy to a literature known procedure: 22 4.85 g (43.7 mmol, 1.00 equiv) of N -hydroxymethanesulfonamide was dissolved in 120 mL of tetrahydrofuran at −78 °C, and 3.82 mL (5.30 g, 52.4 mmol, 1.20 equiv) of triethylamine was added dropwise. After stirring the mixture for 15 min at −78 °C, 3.74 mL (4.11 g, 52.4 mmol, 1.20 equiv) of acetyl chloride was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…N -Acetoxymethanesulfonamide was synthesized in analogy to a literature known procedure: 22 4.85 g (43.7 mmol, 1.00 equiv) of N -hydroxymethanesulfonamide was dissolved in 120 mL of tetrahydrofuran at −78 °C, and 3.82 mL (5.30 g, 52.4 mmol, 1.20 equiv) of triethylamine was added dropwise. After stirring the mixture for 15 min at −78 °C, 3.74 mL (4.11 g, 52.4 mmol, 1.20 equiv) of acetyl chloride was added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…Due to these drawbacks, research in our group 22 and by others (for example, see Scheme 1B) 4 has focused on establishing stable and versatile, hydroxylamine-based, electrophilic amination reagents that are active reagents for non-directed C–H amination reactions. Herein, we report that these reagents can be employed in combination with Cu catalysts to achieve benzylic C sp 3 –H aminations (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…This substrate was selected as a model system based on its modest reactivity under the first generation Pd­(OAc) 2 -catalyzed C–H arylation conditions, which afforded just 46% yield of the C4-arylated product 1a at 150 °C using 30 equiv of PhI as the arylating reagent and solvent (Table , entry 1). Monodentate pyridine-type ligands were explored first based on their well-established utility in enhancing both reactivity and selectivity in related Pd-catalyzed C–H functionalization reactions. However, as shown in Table , the addition of 5 mol % of monodentate pyridine, quinoline, or acridine derivatives L1 – L5 had minimal impact on the yield of 1a (entries 2–6).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of reports from our group 12 and others 13,14,15 have shown that pyridine and carboxylic acid-based ligands can be used to enhance reactivity and modulate selectivity in other Pd-catalyzed C–H functionalization reactions. 16 We demonstrate herein that ligands that combine these two functional groups are effective for increasing the reaction rates, yields, and scope of the Pd-catalyzed transannular C–H functionalization of alicyclic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the methodologies of N‐(fluoroalkyl/fluoroacetyl)‐aniline synthesis include the following; N‐(fluoroalkyl‐/fluoroacetyl)‐aniline can be directly prepared by combination of aniline and trifluoroethylation/trifluoroacetyl reagents (scheme a). Alternatively, the fluoroalkyl/fluoroacetyl group can be introduced by Pd or Cu‐catalyzed coupling of aryl halides and fluoroalkylamine/trifluoroacetamide (scheme b) .…”
Section: Introductionmentioning
confidence: 99%